Family Therapy dalam Gangguan Emosi dan Kenakalan Remaja Pada Anak dari Lingkungan Lahan Rawa - Zainal Fauzi; Sri Ayatina Hayati (Bulletin of Counseling and Psychotherapy, 2022)
This study aims to determine family therapy in emotional disorders and juvenile delinquency. This study covers emotional disorders and juvenile delinquency that occur to students. The results of observations and preliminary studies conducted by researchers at MTsN 1 Banjarmasin juvenile delinquency can arise because there is no acceptance, warmth, protection, uncontrolled anxiety development, depressed mood, and psychological stress. This study uses a quantitative approach with experimental methods. In this study, the experimental design used was "Randomized Pretest-Posttest Comparison Group". The results of the validity test of the Self Reported Delinquency Scale (SRSD) instrument were declared valid on all items with (rxy = 0.510 – 0.860) and an alpha coefficient of 0.751. Meanwhile, the results of the validity test of the Scale for Assessing Emotional Disturbance (SAED) instrument were also declared valid on all items with (rxy = 0.534 – 0.764) and an alpha coefficient of 0.753. The data obtained were then analyzed using the Wilcoxon test, Kruskal Wallis test and gain test. Based on the results of the data analysis above, it can be understood that group counseling services with family therapy are effective in reducing the level of emotional disturbance and juvenile delinquency in MTsN 1 Banjarmasin students. From the results of this study, it is known that family therapy group counseling is proven to be effective in reducing juvenile delinquency and emotional disorders in students of MTsN 1 Banjarmasin. Both experimental groups showed a decreased score after being given treatment, namely family therapy group counseling services.